Laparoscopic surgery for median arcuate ligament syndrome using real‐time stereotactic navigation. Issue 2 (26th September 2021) - Aisu, Yuki; Okada, Tomoaki; Sumii, Atsuhiko; Ganeko, Riki; Okamura, Ryosuke; Nishigori, Tatsuto; Itatani, Yoshiro; Hisamori, Shigeo; Tsunoda, Shigeru; Hida, Koya; Kawada, Kenji; Obama, Kazutaka; et al.
Abstract: Introduction: In median arcuate ligament syndrome (MALS), a hyperplastic MAL causes compression and stenosis of the celiac artery (CA). The treatment involves releasing the external pressure on this artery by dissecting the ligament. However, it is difficult to identify the artery because of its deep anatomical location. Stereotactic navigation provides real‐time information regarding the surgical instrument's location on computed tomography (CT) images. We utilized this system to overcome the difficulty of anatomical identification. Materials and Surgical Technique: We present a case of aneurysm rupture caused by MALS, which was treated with laparoscopic MAL dissection with real‐time stereotactic navigation. Surgery was performed in a hybrid operating room with three‐dimensional C‐arm CT (Artis Zeego, Siemens) and an installed Curve navigation system (BrainLab). Preoperative CT images were aligned with intraoperative C‐arm CT‐like images and the surgical instrument position was projected onto preoperative CT images. After the left gastric artery isolation, the fibrous tissue surrounding the left gastric artery was dissected toward the CA while confirming the location of the CA and aortic wall using the navigation system. The CA's diameter was dilated from 1.8 to 2.6 mm with intraoperative angiography. Discussion: This is the first report of laparoscopic MAL dissection using real‐time stereotactic navigation. Although navigation setting was time‐intensive, this system helped us understand the anatomical structures and in safely and precisely dissecting the MAL.